ASSESSING VISITOR SATISFACTION WITH THE LON MALANG BEACH NATURAL TOURISM ATTRACTION (ODTWA) SAMPANG DISTRICT - Adita Vidya Hayati; Triana Setiyarini (Jurnal Ekonomi, 2023)
Tourism is the largest form of industry in the world, besides that tourism also contributes a lot to the development of the world's economic sector. This can be measured through the country's foreign exchange earnings which have increased more than before, business development, infrastructure, and not only that, tourist attractions can also become jobs for others. This study aims to examine the satisfaction felt by visitors to Lon Beach Malang towards natural tourist attractions. This study uses two variables, namely expectations and performance. The type of research used is descriptive quantitative using data analysis techniques CSI (Consumers Satisfaction Index). The source of data used in this study is primary data in the form of direct interviews with sources, namely visitors to Lon Beach Malang who are being used as goals in this study. The results obtained in the form of results from the calculation of the visitor satisfaction index obtained a result of 74%. These results are between the scale range 0.66 - 0.80.